STATENESS OF POSTSOVIET TERRITORIAL POLITIES - E. Yu. Meleshkina (Сравнительная политика)
Abstract: All post-soviet states face stateness problems, that is why it’s important to reveal their preconditions. The article distinguishes the main factors of state formation in the post-USSR states determining the similarities and differences in the governance problems, the effectiveness of state institutions and rational use of resources. The similarities are explained through the specific nature of post-imperial transition with problems of state and nation-building on top. The differences are determined by the following factors: inclusion into international structures, the number of competing internal and external centers and the degree of tension between centers and cultural-ethnic, regional and economic peripheries, the institutional legacies, the traditions of statehood, resource presence and the degree of political regime consolidation.